Comparison of return to work outcome measures following transport injury. (1st March 2011) - Collie, A; Brion, A; Barker, S; Johnstone, R; Pennay, D
Abstract : Background: Return to work (RTW) is an important marker of recovery from injury. There is substantial evidence that RTW is associated with higher levels of self-rated health, quality of life, greater social inclusion and reduction in ongoing disability. There are multiple RTW metrics reported in the literature and little consensus regarding the most appropriate. Aim: To compare RTW rates following transport injury using a number of criterion. Method: Six-hundred and one individuals (328 males) injured in a transport accident completed a telephone survey between 6 months and 10 years (mean 3.5 years) post injury. Four hundred and forty participants (73.2%) were working at injury, with 289 (48.1%) working >35 h per week. Results: 69.4% of those working at injury had achieved any RTW since injury, with fewer currently working (59.2%) or achieving sustained (57.6%), current and sustained (54.1%) or full RTW (37.6%). RTW rates were greater for those working >35 h per week prior to injury, with 86.9% achieving any RTW and 45.7% achieving a full RTW (defined as >35 h employment per week). In contract, rates in those not working prior to injury were much lower, with 29.2% achieving any RTW and 16.1% achieving a full RTW. RTW rates also varied significantly according to time post injury and occupation. Conclusion: Conclusions regarding injury recovery can vary greatly depending on the RTW criterion utilised and sample characteristics.